Dancescape in Sayaw Barong performance of Bajau Sama - Mohammed Iqbal Badaruddin; Zaimie Sahibil; Luqman Lee; Simon Soon (Penerbit UMS, 2021)
Sayaw barong is one of the traditional performances for the Bajau Sama ethnic in Kota Belud, Sabah. With parang barong itself as a primarily customised weapon, this symbolic performance represents the war dance in Bajau martial arts locally and used as an offensive and defensive technique (buah/jurus silat) that merges in different streams (aliran) of silat such as silat kuntau, silat sping/sprint, silat betawi, and silat Nusantara. Through participants’ observation and performance ethnography, this particular style and technique encompasses the identity of Bajau Sama martial art through artistic movement as a representation that is also performed during other traditions such as wedding ceremonies, traditional healing, or funeral as their own cultural value. By referring to The Fan Theory suggested by Schechner, it shows how this tradition links and connects to other elements in sacred space such as ritualization, shamanism, rites and ceremonies. This paper also discusses the use of parang barong as a material culture and how its appearance helps the efficacy of the performance. The concept of sacred-scapes, death-scapes and kinetic-scapes take shape as tangible and intangible in order to understand this particular custom and how it fits in the Bajau identity as their own art of defence traditions. It also shows the Bajau Sama belief system that creates space in ritual including initiations, customs and celebrations.